2022
DOI: 10.1039/d2en00226d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antifungal evaluation, and safety assessment of mesoporous silica nanoparticles loaded with prothioconazole against crop pathogens

Abstract: Mesoporous silica nanoparticles (MSNs) can be used as carriers to prepare pesticide controlled release formulations with high pesticide loadings and reduce the negative environmental impact of pesticides. In this study,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…[135,136] With an increase in their widespread application there is apprehension over their feasible entry into the environmental food chain and thus having detrimental effects on human health. [137] Some studies substantiate the increased toxicity of nanopesticides at very low concentrations and the toxicity that to of magnitude higher than that of conventional formulations. [138,139] Another challenge that may hinder the industrial scalability of the engineered nanoparticles is the methods to deliver these nanoparticles at targeted locations precisely and cost-effectively.…”
Section: Future Perspectivesmentioning
confidence: 97%
See 1 more Smart Citation
“…[135,136] With an increase in their widespread application there is apprehension over their feasible entry into the environmental food chain and thus having detrimental effects on human health. [137] Some studies substantiate the increased toxicity of nanopesticides at very low concentrations and the toxicity that to of magnitude higher than that of conventional formulations. [138,139] Another challenge that may hinder the industrial scalability of the engineered nanoparticles is the methods to deliver these nanoparticles at targeted locations precisely and cost-effectively.…”
Section: Future Perspectivesmentioning
confidence: 97%
“…Hence, the selection of non‐toxic and easily degradable nanoparticles for the formulation of nanopesticides becomes very important [135,136] . With an increase in their widespread application there is apprehension over their feasible entry into the environmental food chain and thus having detrimental effects on human health [137] . Some studies substantiate the increased toxicity of nanopesticides at very low concentrations and the toxicity that to of magnitude higher than that of conventional formulations [138,139] .…”
Section: Future Perspectivesmentioning
confidence: 99%
“…68,86,126,127 In the case of bare PSN, increasing temperature is reported to enhance release from the carrier. 82,104,105,109 For instance, a wide range of temperature responsiveness (from 25 to 45 °C) on release of tebuconazole from HSN was examined by Qian and co-workers. 109 They observed 80% of pesticide release at the 35th day, 10th day, and 5th day at 25, 35, and 45 °C, respectively.…”
Section: Associated Factors Affecting Release Of Active Molecules Fro...mentioning
confidence: 99%
“…Similar results of lower toxicity from PSNdelivered pesticide on earthworms were also found on several other studies. 82,83 Further, several studies reported reduced phytotoxicity of PSN-delivered pesticides in terms of chromosome aberration (CA) and mitotic index (MI), where a lower CA and higher MI indicate safer molecules. The Vicia faba chromosomal aberration indexes of lambda cyhalothrin EC were 0.21, 0.25, and 0.31 at concentrations of 10, 50, and 100 mg/L, whereas those of dopamine-conjugated MSN-encapsulated lambda cyhalothrin were 0.04, 0.05, and 0.06, respectively, at the same concentration.…”
Section: Improved Pest Control Efficacymentioning
confidence: 99%
See 1 more Smart Citation